Organism and its Aesthetic Connections in the Interior Design: حسنين صباح داوّد سلمان (Al-Academy, 2019)
Organism is considered one of the intellectual products that search for compatibility and harmony with the natural environment. Man has adopted on since the ancient times in choosing his residence through imitating nature such as animal burrows, hives, bird nests and others of the natural manifestations being spontaneous inspirations. With the development of the age, these concepts turned into an analysis that examines the philosophy that deals with the shapes and functions of various elements in the nature as a source of inspiration, and discusses the call for contemplation and achieving benefits physically and spiritually in line with the nature of the organic thought that seeks to keep up with modern technologies that are characterized by the rapid and wide steps in the field of inspiration from nature which has become deeper especially in the last three decades through pairing between different sciences that depend on scientific theories, rules and ideas and the feelings that are inspired by nature. The research introduction presents the methodological framework and then finding concepts and definitions for some terms of the research title. The theoretical framework includes two sections: the first section is a study of the origins and organic ingredients in the interior design. The second section: organism and inspiration by nature and the strategy of using it in the structure of the interior design. The research procedures are supported by some design models that have been analyzed, ending up with a number of results the most important of which: The organic inspiration patterns from nature differed and these differences in the patterns are considered substantial rather formal in the style of expression and presentation. The essence is that nature is the source of organic inspiration. Design in organism in terms of the aesthetic variable is characterized by strangeness and exclusivity. That was the incentive of the aesthetic feeling of the recipient through the possibilities of the organic model design has of visual enrichment resulting from the formation of the systematic design block